Agricultura de precisión : dosis variable de fósforo en soja (Glycine max (L.) Merr.) - Peralta, Nahuel Raúl (2021)
Precision agriculture (AP) allows differentiating management sites (ZM) that express contrasting grain yield potential. The aims of this study were to: i) evaluate the interaction between ZM and phosphorus (P) fertilization oversoybean yield, and ii) quantify the P use efficiency (EUP) in the different ZM. The experience was carried out in two agricultural fields (Site 4 and Site 6) from Benito Juárez. (37°26'53,23"S; 59°35'45,28"O). The ZM were delimited based on the land elevation, topographic index (TWI) and soil depth. The extractable P content (P-Bray) was determined at each ZM after soil sampling. At each ZM, trials with a randomized complete block design (four replications) were performed to evaluate five different P rates(0, 10, 15, 20, 25 kg P ha-1). No interaction between ZM and P fertilization over grain yield was observed. However, the EUP was affected by ZM. The greatest EUP was observed in zones with medium or high productive potential with lower values of P-Bray inthe soil.